Cytological differences between cancer in situ and invasive cervical cancer - Campos Rey de Castro, Jorge (2015)
1900 has been studied cells frotises 50 cases of in situ cervical cancer and 520 cells frotises of 12 cases of invasive cervical cancer, all confirmed histologically. It was performed measurements of each cell and its nucleus and described morphological characteristics and tintoreales nucleus and cytoplasm. It concludes that while there are no cancer cells pathognomonic of cancer in situ, allowing make such a diagnosis for purely cytological means, however smear intra-epithelial carcinoma is usually very suggestive and allows the cytologist, in most cases, advance the possibility of such a diagnosis, which must be confirmed histologically.